IMPLEMENTATION OF MANAGEMENT FUNCTION IN DELI SERDANG SMALL BUSINESSES IN MARKETING MUSLIM PRODUCTS IN NORTH SUMATERA - Uswah Hasanah; Mutiah Khaira Sihotang; Benny Munardi; Khairatun Hisan (Proceeding International Seminar of Islamic Studies, 2021)
Local wisdom in restoring the nation's culture must start from the Indonesian people themselves, especially entrepreneurs or UKM (Small and Medium Enterprises) as the backbone of the nation's economy. The purpose of this study was to determine the application of management functions in the small and medium enterprises of the Deli Serdang community as a strategic area for marketing Muslim products in North Sumatra. The research method uses a qualitative type with a descriptive approach. Data collection techniques were carried out by observation, interviews, and documentation. The results obtained in this study are that the implementation of management functions which include POAC (Planning, Organizing, Actuating, and Controlling) is very effective in the smooth marketing and promotion of products for small and medium enterprises in the Deli Serdang community, this is seen to be significantly assisted by traditional promotion as well. integrating the sophistication of the media in disseminating information. Keywords: Management function,UKM, Marketing of Muslim products.